2023
DOI: 10.1002/smll.202300541
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Surface Chemistry and Morphology of Polymeric Carbon Nitrides Towards Greener Heterogeneous Catalysts for Biodiesel Synthesis

Abstract: Biodiesel remains one of the most promising alternatives to replace fossil fuel‐derived petrodiesel. Nonetheless, conventional biodiesel synthesis relies on homogeneous alkali‐based catalysts that involve long and tedious purification steps , increasing biodiesel production costs. Heterogeneous catalysts have emerged as promising alternatives to circumvent these drawbacks, as they can easily be recovered and reused. Herein, polymeric carbon nitride dots and nanosheets are synthesized through a solid‐phase reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Heterogeneously basic catalyzed transesterifications reported in the literature present molar ratios ranging from 1 : 6 to 1 : 36 oil to methanol. 54,55,67,68 Zhang et al 42 reported the transesterification of castor oil using a carbon-based calcium composite. A conversion of 95% was achieved with a molar ratio of 1 : 18.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneously basic catalyzed transesterifications reported in the literature present molar ratios ranging from 1 : 6 to 1 : 36 oil to methanol. 54,55,67,68 Zhang et al 42 reported the transesterification of castor oil using a carbon-based calcium composite. A conversion of 95% was achieved with a molar ratio of 1 : 18.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that the catalytic mechanism proceeds similarly to homogeneous base-catalyzed transesterification reactions. 54,55,68 Thus, it begins with the nucleophilic attack of methanol on the electrophilic carbonyl of the ester, forming a tetrahedral intermediate zwitterion. Subsequently, a proton transfer from the intermediate to the basic sites on the catalyst surface occurs, enabling the rearrangement to eliminate the alkoxide ion and form the fatty acid methyl ester (FAME).…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that even at low LiK-PHI loading values, such as 0.5%, a significant conversion of 81% is obtained, followed by 1.6 and 2.7 wt % of the catalyst with 94 and 97% of conversion, respectively. de Medeiros et al also studied the catalyst loading ranging from 1 to 7 wt % for the transesterification of canola oil with methanol to produce biodiesel using CNs synthesized from different molar ratios of urea and sodium citrate . The authors showed that the catalyst loads of 1, 3, 5, and 7% have 0.41, 2.86, 97.5, and 98.0% of reaction yield, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, for mpg-C 3 N 4 , symmetrical pores were recognized in its flake structure. A variety of CN-based nanomaterials have been previously studied in the literature, and all of them presented layer/flake morphology with unique characteristics. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation